Examination of hemodynamics in patients in hemorrhagic shock undergoing Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA). Issue 5 (May 2019) - Wasicek, Philip J.; Li, Yao; Yang, Shiming; Teeter, William A.; Scalea, Thomas M.; Hu, Peter; Brenner, Megan L.
Highlights: Significant hemodynamic changes occurred in patients with Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA). The effects of Zone 1 REBOA on blood pressure and heart rate appear different than Zone 3. Significant hemodynamic variability with episodes of hypertension and hypotension occurred in a large proportion of cases during REBOA. There may be a precipitous decrease in blood pressure that should be anticipated following balloon deflation of the REBOA catheter. Abstract: Background: The objective of this study was to investigate the hemodynamic effects of aortic occlusion (AO) during Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) using a sophisticated continuous vital sign (CVS) monitoring tool. Methods: Patients admitted between February 2013 and May 2017 at a tertiary center that received REBOA were included. Patients in cardiac arrest before or at the time of REBOA were excluded. Time of AO was documented by time-stamped videography and correlated with CVS data. Results: 28 patients were included, mean (standard deviation) ISS was 38 (11). 18 received Zone 1 (distal thoracic aorta) and 10 received Zone 3 (distal abdominal aorta) AO. Among Zone 1 patients the pre-AO systolic blood pressure (SBP) nadir was 64 (19) mmHg, which increased to a mean of 124 (29) mmHg within 5 min after AO (p < 0.01). Among Zone 3 patients the pre-AO SBP nadir was 75 (19) mmHg, which increased to a mean of 98 (14) mmHg within 5 min after AO (p < 0.01). 72% of Zone 1 patients had episodes during AO where SBP was less than 90 mmHg as compared to 80% of Zone 3 patients (p = 0.51). 100% of Zone 1 patients had periods during AO where SBP was greater than 140 mmHg as compared to 70% Zone 3 patients (p = 0.04). The overall mean decrease in SBP after balloon deflation was 13 (20) mmHg (p < 0.01), with similar decreases among groups (14 (21) mmHg vs 12 (18) mmHg for Zone 1 and 3 patients, respectively (p = 0.85)). Patients undergoing Zone 1 AO were more likely to have an acute change (increase or decrease) in their heart rate immediately after AO as compared to Zone 3 AO (p = 0.048). Conclusions: Significant hemodynamic alterations occur before, during, and after AO. The effects of Zone 1 AO on blood pressure and heart rate appear different than Zone 3 AO. This may have important implications for cardiac or cerebral function and perfusion goals, particularly with concomitant injuries such as cardiac contusion or traumatic brain injury.